2017
DOI: 10.1371/journal.pone.0175327
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and central immune cell reservoirs in tissues from asymptomatic cats chronically infected with feline immunodeficiency virus

Abstract: Feline immunodeficiency virus (FIV) infection in cats results in life-long viral persistence and progressive immunopathology. We have previously described a cohort of experimentally infected cats demonstrating a progressive decline of peripheral blood CD4+ T-cell over six years in the face of apparent peripheral viral latency. More recently we reported findings from this same cohort that revealed popliteal lymph node tissue as sites for ongoing viral replication suggesting that tissue reservoirs are important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…These observations suggested a proliferation of resident of Tfh cells or infiltration of CD8+ T cells into the B cell follicles, although CD8+ T cells are generally restricted from entering B cell follicles. Secondly, in our most recent report, a novel in situ hybridization technique (RNAscope) for detection of FIV RNA identified germinal centres in the mesenteric lymph node, spleen and intestinal Peyer's patches as microanatomical reservoirs of viral transcription in the chronically FIV-infected cat [92].…”
Section: Fiv Tissue Reservoirsmentioning
confidence: 92%
See 3 more Smart Citations
“…These observations suggested a proliferation of resident of Tfh cells or infiltration of CD8+ T cells into the B cell follicles, although CD8+ T cells are generally restricted from entering B cell follicles. Secondly, in our most recent report, a novel in situ hybridization technique (RNAscope) for detection of FIV RNA identified germinal centres in the mesenteric lymph node, spleen and intestinal Peyer's patches as microanatomical reservoirs of viral transcription in the chronically FIV-infected cat [92].…”
Section: Fiv Tissue Reservoirsmentioning
confidence: 92%
“…Anatomical reservoirs frequently discussed in the HIV field are the brain, gut-associated lymphoid tissue (GALT), lymph nodes and the reproductive tract [13,14,88,91]. Many of these tissues have been investigated as tissue reservoirs in the FIV-infected cat as well, particularly during the acute and early asymptomatic phases of infection [60,62,79,92]. A thorough understanding of tissue reservoir distribution and biology requires an understanding of the early pathogenesis and dissemination of virus.…”
Section: Fiv Tissue Reservoirsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in a recent study CD4 + and CD21 + leukocytes were identified as cellular reservoirs for FIV replication which is similar to the subsets identified in HIV infection wherein CD4 + T cells serve as cellular reservoirs and CD21 + B cells serve as extracellular HIV reservoirs [ 48 , 49 ]. The same study identified FIV reservoirs in tissues such as the spleen, the intestine and mesenteric lymph node with B cell follicles as the foci of viral replication in chronically infected cats exhibiting viral latency [ 50 ]. This demonstrates that the FIV model offers the advantage of performing longitudinal infection studies which can be beneficial in understanding tissue viral reservoir dynamics [ 50 ].…”
Section: Animal Models Of Hiv Infection To Study Cd8 + mentioning
confidence: 99%